Envejecer en la Zona Metropolitana del Valle de México: memoria, representaciones socioespaciales y género - de Alba González, Martha (El Colegio de México A.C., 2023)
This article presents results of a survey about memories, social representations and experiences about Mexico City of 101 elderly living in different neighborhoods of Mexico City Metropolitan Area. Content analysis of interviews and cognitive maps suggest a relationship between urban expansion and getting old process. Social representations of the city are linked to family, residential, work and education trajectories of the informant’s life course. We also find gender differences in experiencing and imagining the city. The results of this research help to understand the process of getting older in big cities.